Reduced scapular neck impingement in 145° neck-shaft angle semi-inlay compared with 155° neck-shaft angle inlay reverse total shoulder arthroplasty during active external rotation - Itaru Kawashima, MD, PhD; Norimasa Takahashi, MD, PhD; Keisuke Matsuki, MD, PhD; Ryo Haraguchi, MD; Hayato Ryoki, MD; Thomas W. Wright, MD; Scott A. Banks, PhD (JSES International)
Background: The purpose of this study was to measure the distance between the scapular neck and the humeral polyethylene insert in shoulders with a 145° neck-shaft-angle (NSA) semi-inlay reverse total shoulder arthroplasty (rTSA) during active external rotation and to compare it with the distance in shoulders with a 155° NSA inlay rTSA. Methods: Twenty shoulders with 145° NSA semi-inlay rTSA and 18 shoulders with 155° NSA inlay rTSA were analyzed. Each shoulder underwent computed tomography and fluoroscopy. Fluoroscopic images were acquired during the activity, starting from internal rotation at the side and progressing to maximum external rotation, while keeping the shoulder adducted. Using model-image registration techniques, the poses of 3-dimensional models were iteratively adjusted to match their silhouettes with those in the fluoroscopic images. Based on the 3-dimensional kinematics of the implants, the closest distance between the scapular neck and polyethylene insert was computed. The data from 10° internal rotation to 50° external rotation were used for analysis. It was also evaluated whether the distance approached within 1 mm, as it was considered that impingement occurred between the scapular neck and polyethylene insert at this proximity. Results: The distance between the scapular neck and the polyethylene insert significantly decreased as the shoulder externally rotated (P < .001). This distance was significantly larger in shoulders with semi-inlay rTSA compared to those with inlay rTSA (P < .001). The rate of shoulders that approached within 1 mm of distance during activity was significantly lower in the semi-inlay rTSA group than in the inlay rTSA group [20.0% (4/20) vs. 83.3% (15/18), respectively, P < .001]. Conclusions: The distance between the scapular neck and the polyethylene insert during active external rotation was greater in a 145° NSA semi-inlay rTSA compared to a 155° NSA inlay rTSA. This study supports the notion that a 145° NSA semi-inlay rTSA significantly reduces scapular notching compared to a 155° NSA inlay rTSA. However, scapular notching, especially caused by maximum external rotation, should still be considered in shoulders with a 145° NSA semi-inlay rTSA as well, as the distance significantly decreases during external rotation.